Genotypic Variation in a Breeding Population of Yellow Sweet Clover (Melilotus officinalis) - Luo, Kai; Jahufer, M. Z. Z.; Wu, Fan; Di, Hongyan; Zhang, Daiyu; Meng, Xuanchen; Zhang, Jiyu; Wang, Yanrong (Frontiers in Plant Science, 2016)
Yellow sweet clover is a widely spread legume species that has potential to be used as a forage crop in Western China. However, limited information is available on the genetic variation for herbage yield, key morphological traits and coumarin content. In this study, 40 half sib (HS) families of M. officinalis were evaluated for genotypic variation and phenotypic and genotypic correlation for the traits: LS (leaf to stem ratio), SV (spring vigour), LA (leaf area), PH (plant height), DW (herbage dry weight), SD (stem diameter), SN (stem number), Cou (coumarin content), SY (seed yield), across two locations, Yuzhong and Linze, in Western China. There was significant (P<0.05) genotypic variation among the HS families for all traits. There was also significant (P<0.05) genotype-by-environment interaction for the traits DW, PH, SD, SN and SV. The estimates of HS family mean repeatability across two locations ranged from 0.32 for SN to 0.89 for LA. Pattern analysis generated four HS family groups where group 3 consisted of families with above average expression for DW and below average expression for Cou. The breeding population developed by polycrossing the selected HS families within group 3 will provide a significant breeding pool for M. officinalis cultivar development in China.